Islamic Dialogue, Local Culture, and Women in Sigi Regency, Indonesia - Nuraedah (International Journal of Criminology and Sociology, 2022)
This research describes the tradition, Islam, women, and local culture in Sigi Regency through the sociological and historical approach. Tradition, Islam, local culture, and women were objects, and subjects were investigated to describe daily lives around the Islamic Boarding School (Pesantren). Women were the object of the study because they are more sensitive and vulnerable to the development of local traditions. Women’s daily activities showed resistance against the domination of men over women. The reality in the society of the district of Sigi showed that women have a substantial contribution as a mediator who served as a liaison, and communicator between Islamic boarding School (pesantren) ’s interest’ and community’s interests. It is most apparent when women contribute to religious activities that were carried out by Islamic Boarding School (Pesantren) and the community.